2022
DOI: 10.1186/s40168-022-01289-w
|View full text |Cite
|
Sign up to set email alerts
|

Gut dysbiosis promotes prostate cancer progression and docetaxel resistance via activating NF-κB-IL6-STAT3 axis

Abstract: Background The gut microbiota is reportedly involved in the progression and chemoresistance of various human malignancies. However, the underlying mechanisms behind how it exerts some effect on prostate cancer, as an extra-intestinal tumor, in a contact-independent way remain elusive and deserve exploration. Antibiotic exposure, one of the various factors affecting the gut microbiota community and capable of causing gut dysbiosis, is associated with multiple disorders. This study aims to prelim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(60 citation statements)
references
References 51 publications
0
50
0
Order By: Relevance
“…For example, gut microbes produce sex hormones, such as androgen, and, in a study by Pernigoni et al, multiple species among mice and humans produced androgens from androgen precursors, in turn promoting progression of castrate resistant PCa [ 107 ]. In a study of both mice and PCa patients, Proteobacteria was increased after antibiotic exposure, and was in turn associated with development of PCa in mice and with metastasis of PCa among humans [ 108 ]. In a study of mice on a high-fat diet, the resultant alterations to the mice fecal microbiome promoted histamine biosynthesis and increased inflammatory cancer cell growth [ 109 ].…”
Section: The Gut Microbiome Pca and Gtcsmentioning
confidence: 99%
“…For example, gut microbes produce sex hormones, such as androgen, and, in a study by Pernigoni et al, multiple species among mice and humans produced androgens from androgen precursors, in turn promoting progression of castrate resistant PCa [ 107 ]. In a study of both mice and PCa patients, Proteobacteria was increased after antibiotic exposure, and was in turn associated with development of PCa in mice and with metastasis of PCa among humans [ 108 ]. In a study of mice on a high-fat diet, the resultant alterations to the mice fecal microbiome promoted histamine biosynthesis and increased inflammatory cancer cell growth [ 109 ].…”
Section: The Gut Microbiome Pca and Gtcsmentioning
confidence: 99%
“…The results of previous studies have demonstrated that inflammation could lead to chemoresistance of cancer cells (17,33). Zhong et al revealed that the NF-κB-IL6-STAT3 axis activated by intratumoral LPS promoted the expression of cyclin D1, c-Myc, Bcl-2 and survivin, facilitating prostate cancer proliferation and docetaxel chemoresistance (33). Neddylation-inhibitor MLN4924 exhibits broad anticancer potential and may be used as a chemotherapeutic agent in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Dysbiosis is often associated with an increase in gut permeability and endotoxinemia, which is an increase in the circulating level of bacterial lipopolysaccharide (LPS) [ 10 , 11 ]. In mice, dysbiosis induced by broad-spectrum antibiotics favors the accumulation of LPS in subcutaneous and orthotopic PC, thereby activating local inflammation and promoting tumor growth [ 12 ]. High fat diet-induced dysbiosis also triggers an LPS-mediated pro-inflammatory pathway secondary to the LPS-induced upregulation of the histamine-producing enzyme histidine decarboxylase (HDC) in mast cells infiltrating the tumor [ 13 ].…”
Section: Contribution Of the Intestinal Microbiota To Prostate Carcin...mentioning
confidence: 99%
“…Such studies are urgently awaited. Of note, in PC patients, the fecal abundance of Proteobacteria correlates with the presence of distant metastases [ 12 ]. Thus, there is circumstantial evidence suggesting that intestinal dysbiosis contributes to prostate carcinogenesis and tumor progression ( Fig.…”
Section: Contribution Of the Intestinal Microbiota To Prostate Carcin...mentioning
confidence: 99%